Tafsir Indonesia di Rezim Otoritarianisme - Ihsan Nursidik (UIN Sunan Gunung Djati Bandung, 2021)
Authoritarianism is a government-controlled by absolute power in one person. This kind of government has occurred in Indonesia to precisely what is known as the Old Order and the New Order. It is in this regime that the influences to maintain power are massively infiltrated as discourse. Among these infiltrations, the activity of interpreting the Koran was also involved in the effort to dominate the political stage at that time. The interpretation of the Koran is one of the domains for producing regime discourse and movements to criticize it. This research is a literature study using descriptive qualitative research methods. In this research, authoritarianism has become a kind of field of meaning that affects the public sphere at that time. So that the actors involved in it, produce an understanding of the Koran based on the influence of the effects of authoritarianism that accompanied it at that time.